2018
DOI: 10.21474/ijar01/6596
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Floppy Eyelid Syndrome and Its Ophthalmic and Systemic Associations.

Abstract: Introduction: Floppy eyelid syndrome (FES) is characterized by very elastic upper lids that became easily distorted and evertible with minimal lateral traction and chronic papillary conjunctivitis of the upper palpebral conjunctiva. Apart from various ocular associations, FES has been associated with various systemic diseases like obesity, hypertension, IHD and DM. The present study was thus planned to gather data regarding the prevalence of FES and its ocular and systemic associations in the local population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Of the included patients, 368 were male (77.6%) and the average age was 55.10 years. The current study included 4 prospective non-randomized cross-sectional observational studies, 24-27 7 retrospective analyses, 8,28-33 and 1 case-control study. 5 The overall prevalence of OSA in FES was 57.1% (95% CI: 46.5–74.8%), shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included patients, 368 were male (77.6%) and the average age was 55.10 years. The current study included 4 prospective non-randomized cross-sectional observational studies, 24-27 7 retrospective analyses, 8,28-33 and 1 case-control study. 5 The overall prevalence of OSA in FES was 57.1% (95% CI: 46.5–74.8%), shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…FES as an outcome of OSA was initially suggested by Culbertson and Tseng in 1994 6 when describing hypoxic tissue in OSA patients, and corroborated by McNab when the treatment of OSA in a 32-year-old male reversed FES. Since then, 1 case-control study by Ezra et al 5 has demonstrated a significant association of FES with OSA, but other retrospective 8,[27][28][29][30][31][32][33] and prospective studies [24][25][26] have also observed this link. The strongest hypothesis bridging these conditions relates to the chronic, transient, hypoxic, and reperfusion insults posed on the vasculature as a result of frequent apnea while a person with OSA is asleep.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations